Perancangan Interior Klinik Kecantikan Berbasis Eco-Design di Surabaya - Andereas Pandu S., Novian Wibowo (Intra, 2013)
Beauty clinic is a place that provides professional services related to beauty and skin care, including skin rejuvenation process, enlightenment skin, and correct any deficiencies that appear on the skin. Design beauty clinics that implement Eco-Design is a clinic which in technical terms and activities hold the principles of eco-design. For example, the formation and stylish design, the atmosphere in the interior space, material selection, lighting systems, ventilation systems and other interior support system has been certified eco-friendly. Designed facility includes lobby, waiting room, doctors consulting room, examining room, treatment room, laser room, VIP room, service area employees, offices, meeting rooms, and a cafeteria area. Concept design eco design.Desain taken is environmental friendly, hygienic, and easy in terms of design perawatan.Tema used is clean and sejuk.Karakter clean design embodies the impression of a clinic in general, while the impression of a cool space adapted to the tropical climate in the city of Surabaya.